Tradisi papungu tumpak ulaon borngin pada masyarakat sahil jae - Tia Ningsi Sarumpaet; Torang Naiborhu; Rahmatika L Sholikha (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study discusses the Papungu Tumpak Ulaon Borngin tradition in the Sahil Jae Village community, Sorkam District, Central Tapanuli Regency, which is part of a series of traditional Batak Toba wedding ceremonies. The problem of this research is how the ceremony runs and how the form of presentation and function of music in the Papungu Tumpak Ulaon Borngin party. This study aims to describe the stages of the ceremony, the form of music presentation, and the function of music in the context of the traditional ritual. The method used is a qualitative descriptive method with an ethnomusicological approach. Data were collected through direct observation, interviews with traditional leaders, musicians, and local residents, and documentation in the form of photos, audio, and video. The results of the study show that the Papungu Tumpak Ulaon Borngin party is held the night before the traditional wedding ceremony and consists of several stages, such as manomu-nomu, pasahat tumpak, pasahat silua, marpanganan borngin, distribution of jambar, and entertainment events. Music has an important role as an accompaniment to traditional processions, a means of symbolic communication, and a medium of entertainment for the community. Thus, music not only functions as an aesthetic element, but also as a means of strengthening social solidarity, conveying traditional messages, and preserving the cultural identity of the Toba Batak people in Sahil Jae Village